T.S. Eliot and R.V. Scruton: Common pursuit of true judgement - Sławkowski-Rode, Mikołaj (Przegląd Filozoficzny. Nowa Seria, 2020)
Roger Scruton refers to Thomas Stearns Eliot in almost every one of his books, but despite the undoubtedly fundamental influence, which Eliot had exerted on the development of Scruton’s outlook, apart from a short article entitled Eliot and Conservatism, Scruton did not devote a separate work to Eliot’s thought. As I try to show this is due to the fact that Scruton was not so much a scholar of Eliot, as a continuator of his thought – not merely an expert on his philosophy and poetry, but an inheritor of his spiritual legacy. Both Eliot and Scruton belong to a current, which may rightly be called conservative philosophy of culture. In this paper I outline the conception of culture advanced by Eliot, and show how Scruton draws on this conception in his own spiritual development.
Keywords: T.S. Eliot; R. Scruton; culture; experience; religion; individual; community